Effects of vitamin C supplementation with and without endurance physical activity on components of metabolic syndrome: A randomized, double-blind, placebo-controlled clinical trial. (August 2019) - Farag, Halgord Ali M.; Hosseinzadeh-Attar, Mohammad Javad; Muhammad, Belal A.; Esmaillzadeh, Ahmad; El Bilbeisi, Abdel Hamid
Summary: Background & aims: Metabolic syndrome is a cluster of the most dangerous heart attack risk factors. The present study aimed to examine the effects of vitamin C supplementation with and without endurance physical activity on components of metabolic syndrome in a group of Iraqi adults. Methods: In a parallel-randomized placebo controlled trial, 120 metabolic syndrome patients were randomly assigned into four groups. Fasting blood samples were taken at study baseline and after 12 weeks of intervention. All statistical analysis was performed using SPSS version 20. Results: The mean vitamin C levels was increased significantly in both vitamin C and vitamin C plus physical activity groups (P value = 0.001). Vitamin C plus physical activity led to a significant reduction in systolic blood pressure compared to the placebo group (P value = 0.04). In addition, a significant changes in serum levels of total cholesterol were seen following vitamin C plus physical activity than that in the placebo group (P value = 0.04). Furthermore, vitamin C supplementation significantly affected BMI compared with the placebo group (P value = 0.02). No significant differences were found between the study groups in terms of triglyceride, LDL-C, HDL-C, fasting blood sugar, weight, waist circumference and diastolic blood pressure. Conclusion: Daily supplementation of vitamin C (500 mg/day), for 12 weeks resulted in a significant reduction in BMI. However, the combination of physical activities and vitamin C supplements may improve systolic blood pressure and serum levels of total cholesterol in metabolic syndrome patients and this combination should be recommended. Trial registration: WHO-ICTRP, IRCT20161110030823N2. Registered 01 February 2018, http://apps.who.int/trialsearch/Trial2.aspx?TrialID=IRCT20161110030823N2 .